Genetic Creutzfeldt-Jakob disease shows fatal family insomnia phenotype. Issue 1 (1st January 2021) - Chen, Bin; Zhang, Shan; Xiao, Ying; Wu, yingman; Tang, Weiting; Yan, Limin; Zhang, Zhengxue; Qin, Shengquan; Dai, Mingming; You, Yong
ABSTRACT: We report a case of genetic Creutzfeldt-Jakob disease (gCJD), which has a clinical phenotype that is highly similar to Fatal Family Insomnia (FFI) and has a triad of Wernicke-Korsakoff syndrome (WKs) at the developmental stage of the disease. The 51-year-old male complained of sleep disorder and imbalance who had visited five different hospitals before diagnosed. A neurological examination revealed a triad of symptoms characteristic for WKs such as gaze paresis, ataxia of limbs and trunk, and memory disturbances. The disturbances increased during the course of the disease, which led to the death of the patient 18 months after the appearance of the signs. Although the patient show negative in brain magnetic resonance imaging (MRI) and 14-3-3 protein of cerebrospinal fluid (CSF), he was finally diagnosed with gCJD disease by the human prion protein (PRNP) gene mutations.